Photosynthetic microalgae-mediated transformation of hexahydro-1,3,5-trinitro-1,3,5-triazine under initially anaerobic conditions - Hwang, Yun Ho; Yun, Seong-Taek; Lee, Seunghak; Kwon, Man Jae (WILEY, 2018)
We examined the potential of photosynthetic microalgae to perform anaerobic transformation of an energetic explosive compound, hexahydro-1,3,5-trinito-1,3,5-triazine (RDX). All species tested, including Microcystis sp., Pediastrum biwae, Nostoc commune, and Scenedesmus obliquus, exhibited the potential for RDX transformation under light and initially anaerobic conditions; 40 mu M (approximate to 8.9 mg L-1) of RDX decreased to 0 approximate to 7 mu M within 7 d. The formation and subsequent removal of nitrite and ammonium occurred after RDX transformation in the presence of S. obliquus under light and anaerobic conditions. Significantly more RDX was transformed when incubated with S. obliquus than without microalgae, likely because the cells used RDX and its metabolites as carbon and nitrogen sources. In the absence of microalgae, RDX concentrations decreased by <5%, 40%, and 75% at light intensities of 0, 25, and 50 mu mol s(-1) m(-2), respectively, within 15 d, and nitrite as a byproduct of RDX transformation was detected only under light conditions. This suggested that RDX transformation occurred not only by enzymatic transformation but also through an initial denitration pathway via photodegradation. This study demonstrates that photosynthetic microalgae can transform RDX and its intermediates effectively under light and anaerobic conditions, and suggests that photosynthetic microalgae are a viable option for treating RDX-contaminated wastewater. (c) 2017 American Institute of Chemical Engineers Environ Prog, 37: 1677-1683, 2018
Keywords: NITRAMINE EXPLOSIVES RDX; WASTE-WATER; DEGRADATION PATHWAYS; NOSTOC-COMMUNE; BIODEGRADATION; REMOVAL; CL-20; TNT; BIOTRANSFORMATION; PHOTODEGRADATION